PENGARUH SARANA DAN PRASARANA TERHADAP MOTIVASI BELAJAR SISWA DI SDN SEMPU 2 - Reksa Adya Pribadi; Nabilla Cholifiana Putri; Ninis Cholisotun Nisa; Sekar Nadya Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
In education, it is important to have facilities and infrastructure to support the learning process, such as classrooms, learning tools or media, libraries, and so on. Therefore, there is a need for management or administration to regulate facilities and infrastructure in education. Starting from procuring facilities and infrastructure in schools, checking facilities and infrastructure that are still considered incomplete, and so on. The location or place that was targeted in this research was an elementary school, specifically SDN Sempu 2, Serang City. In this research, researchers used descriptive qualitative research methods, where in this research researchers tended to use analysis or direct observation. Adequate facilities and infrastructure also influence student learning motivation. If the facilities and infrastructure are complete, then students' motivation to learn will be more active, enjoyable and comfortable. Students become happy in carrying out the learning process.